Narcissistic coaches and athletes` individual rowing performance - Nevicka, B.; van Gerven, E. J. G.; Sedikides, C. (Scientific Reports, 2023)
Narcissism, a personality trait marked by an excessively self-aggrandizing, entitled, and dominant orientation, has been associated with high performance under competitive pressure, as these contexts afford the opportunity to self-enhance. Narcissism is often characteristic of organizational and political leaders, yet little is known about narcissism in sports coaches. We propose that in a competitive context narcissistic coaches could inspire and motivate their athletes to raise their performance. We investigated the association between coach narcissism and athletes` performance, and the role of athletes` perceived self-enhancement opportunity as a potential mediating mechanism. We examined coach narcissism, athletes` individual end times (i.e., performance), and athletes` perceptions of self-enhancement opportunity during annual national indoor rowing competitions in 266 national level competitive rowers from 52 rowing clubs. Results of multilevel analyses showed that coach narcissism positively predicted athlete performance, and this was explained by athletes` perceived opportunity to self-enhance during the competition. Thus, narcissistic coaches seem to reinforce athletes` perceptions that competition provides them with an opportunity to show off their skills, which in turn accounts for athletes` better performance in comparison to athletes who do not train with narcissistic coaches. The findings point to a potentially functional side of narcissism in coaching.